Anness, Sedgwick County - Jackson, Alex (Kansas State University, The Chapman Center for Rural Studies, 2011)
W.H. Wilson founded Anness in the 1880s, in what is now southwestern Sedgwick County. Named after his wife Ann and born out of the overstepping railroad into his farmland. The farm community of Anness never flourished to more than 100 residents and lost it's hold to the automobile and growing town of Wichita. The post office of Anness now sits as part of a tourist attraction in Wichita's Cowtown.
Alex Jackson, “Anness, Sedgwick County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/17.
Keywords: Anness; Sante Fe Railroad; Sedgwick County; W.H. Wilson; Alex Jackson